PENGARUH DUA DIMENSI PENGANGGARAN PARTISIPATIF TERHADAP SLACK ANGGARAN DENGAN TRUST SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pemerintah Kota Cilegon) - Ulyadi . (Jurnal Akuntansi Aktual, 2016)
Abstract:This research purposes to examine and analyze the effect of two-dimensional on participa-tory budgeting to the budgetary slack through trusts. The research proves that the influence of the twodimensions of participatory budgeting only budget influence that can reducebudgetary slack, the two-dimensional on participatory budgeting can enhance trust regulator-budgeting and trust can reducethe potential slack in the budget formulation, but trust is not an intervening variable between the two-dimensional on participatory budgeting with budgetary slack.Keywords: trust, budgetary slack,psychological contract theory